(3JGQjN fLOs - (3ebHd Hf YHO GdYRjR GdPcjQ , fMh (B1360 (3g`s
(3ChdgG (B:s
(3ai SfI (B1059 (3Jhai GdTjN GdEeGe eMeO Hf CMeO Hf ESeGYjd s
(3BNQgG (B:s
(3YHOGdYRjR Hf eJYH GdQTjO s
(3ef GdfSNI faSgGs
(3HChdgG agQSJs
(3hHYVgG ecJhH HGdBdI GdcGJHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B281s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B89 s
Keywords: (3GdJGQjNs